Estimation of the Content of Selected Active Substances in Primary and Secondary Herbal Brews by UV-VIS and GC-MS Spectroscopic Analyses - Jakub Wyrostek; Radosław Kowalski; Urszula Pankiewicz; Ewa Solarska (Journal of Analytical Methods in Chemistry)
Primary and secondary herbal brews were tested for the content of polyphenolic compounds, flavonoids, and essential oil. The brewing process was carried out at an initial temperature of 95°C and different time parameters (5, 10, 15, and 30 min). A secondary brewing was also carried out to estimate the reuse of the herbal material. The highest content of polyphenol compounds and flavonoids was determined in the primary peppermint brews (4017 mg L−1 and 360 mg L−1, respectively). The secondary brews were characterised by a lower content of active substances than the primary brews. The study showed that the herbal postbrewing material contained significant levels of essential oil (from 13.04% to 95.65%) and may be an alternative source of volatile bioactive compounds.